Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.2174/156802606775193293
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase: Molecular Modeling with the Whole Toolkit

Abstract: Molecular modeling efforts aimed at probing the structure, function and inhibition of the acetylcholinesterase enzyme have abounded in the last decade, largely because of the system's importance to medical conditions such as myasthenia gravis, Alzheimer's disease and Parkinson's disease, and well as its famous toxicological susceptibility to nerve agents. The complexity inherent in such a system with multiple complementary binding sites, critical dynamic effects and intricate mechanisms for enzymatic function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 102 publications
(134 reference statements)
0
16
0
Order By: Relevance
“…The grid for docking was generated by Autodock tools (ADT) (Sanner, 1999) by centring the grid on the co-crystallized inhibitor present in the crystal structures downloaded. Only in the case of acetylcholinesterase, the binding pocket was centred around the residues His447, covering all the residues reported in literature to be part of the enzymatic pocket: Ser203, Glu334, Tyr124, Trp286, Tyr341, Asp74 (Lushington et al, 2006). The rotable bonds of (-)-epicatechin were selected by default.…”
Section: Docking Experimentsmentioning
confidence: 99%
“…The grid for docking was generated by Autodock tools (ADT) (Sanner, 1999) by centring the grid on the co-crystallized inhibitor present in the crystal structures downloaded. Only in the case of acetylcholinesterase, the binding pocket was centred around the residues His447, covering all the residues reported in literature to be part of the enzymatic pocket: Ser203, Glu334, Tyr124, Trp286, Tyr341, Asp74 (Lushington et al, 2006). The rotable bonds of (-)-epicatechin were selected by default.…”
Section: Docking Experimentsmentioning
confidence: 99%
“…3), so determining which structure the known inhibitors are binding to is complicated. The basic rationale for the need to include molecular dynamics in the development of enzyme inhibitors for the related AChE has been recently reviewed 33) . This rationale also applies to CEs.…”
Section: In Silico Methods and Development Of Isatinsmentioning
confidence: 99%
“…Generic docking of known AChE inhibitors to a static AChE are generally not predictive for the relative magnitudes of the inhibition constants 33) . This has been attributed to the inability of static models to correctly calculate the entropy change upon inhibitor binding.…”
Section: In Silico Methods and Development Of Isatinsmentioning
confidence: 99%
“…The use of MD in the development of enzyme inhibitors for the related α/β hydrolase acetylcholinesterase (AChE) has been recently reviewed [17] and these principles also apply to CEs. Briefly, enzymes are in constant motion at temperatures near 37°C and the understanding of the fluctuation is crucial for understanding of the interactions of the enzyme with its substrate or inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Acetylcholinesterase has been the subject of considerable MD simulation for the reasons given above (reviewed in [17, 19]). In contrast, only a few studies of the MD of CEs have been reported [16, 20, 21].…”
Section: Introductionmentioning
confidence: 99%